The Opioid-Sparing Effect of Perioperative Dexmedetomidine Plus Sufentanil Infusion during Neurosurgery: A Retrospective Study - Su, Shiyu; Ren, Chunguang; Zhang, Hongquan; Liu, Zhong; Zhang, Zongwang (Frontiers in Pharmacology, 2016)
Background: Approximately 60% of patients experience moderate-to-severe pain after neurosurgery, which primarily occurs in the first 24–72 h. Despite this, improved postoperative analgesia solutions after neurosurgery have not yet been devised. This retrospective study was conducted to evaluate the effect of intra- and postoperative infusions of dexmedetomidine (DEX) plus sufentanil on the quality of postoperative analgesia in patients undergoing neurosurgery. Methods: One hundred and sixty-three post-neurosurgery patients were divided into two groups: Group D (DEX infusion at 0.5 μg·kg–1 for 10 min, then adjusted to 0.3 μg·kg–1·h–1 until incision suturing) and Group ND (no DEX infusion during surgery). Patient-controlled analgesia was administered for 72 h after surgery (Group D: sufentanil 0.02 μg·kg–1·h–1 plus DEX 0.02 μg·kg–1·h–1, Group ND: sufentanil 0.02 μg·kg–1·h–1) in this retrospective study. The primary outcome measure was postoperative sufentanil consumption. Hemodynamics, requirement of narcotic and vasoactive drugs, recovery time and the incidence of concerning adverse effects were recorded. Pain intensity (Visual Analogue Scale [VAS]), Ramsay sedation scale (RSS) and Bruggemann comfort scale (BCS) were also evaluated at 1, 4, 8, 12, 24, 48, and 72 h after surgery. Results: Postoperative sufentanil consumption was significantly lower in Group D during the first 72 h after surgery (P<0.05). Compared with Group ND, heart rate (HR) in Group D was significantly decreased from intubation to 20 min after arriving at post anesthesia care unit (PACU), while mean arterial pressure (MAP) in Group D was significantly decreased from intubation to 5 min after arriving at PACU (P<0.05). The intraoperative requirements for sevoflurane, remifentanil and fentanyl were approximately 35% less in Group D compared with Group ND. VAS at rest at 1, 4, and 8 h and with cough at 12, 24, 48, and 72 h after surgery were significantly lower in Group D (P<0.05). Compared with Group ND, patients in Group D showed lower levels of overall incidence of tachycardia, hypertension, nausea and vomiting (P<0.05). There were no significant differences between the two groups in terms of baseline clinical characteristics, recovery time, RSS and BCS (P>0.05). Conclusions: DEX (0.02 μg·kg–1·h–1) plus sufentanil (0.02 μg·kg–1·h–1) could reduce postoperative opioid consumption and concerning